2015
DOI: 10.1017/s1368980014003097
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between amount of soda consumed and intention to reduce soda consumption among adults exposed to the Choose Health LA ‘Sugar Pack’ health marketing campaign

Abstract: Objective: To examine behavioural intention to reduce soda consumption after exposure to the Choose Health LA 'Sugar Pack' campaign in Los Angeles County, California, USA. Design: A cross-sectional street-intercept survey was conducted to assess knowledge, attitudes, health behaviours and behavioural intentions after exposure to the 'Sugar Pack' campaign. A multivariable regression analysis was performed to examine the relationships between the amount of soda consumed and selfreported intention to reduce consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 44 publications
2
15
0
Order By: Relevance
“…Similar positive impacts of being exposed to a campaign focussing on the importance of reducing the consumption of SSBs were also reported in two cross-sectional studies conducted in the US (Barragan et al, 2014;Robles et al, 2015). One of them (Barragan et al, 2014) reported more than twice the likelihood of correctly reporting the quantity of sugar in a soda drink (OR 2.63, 95%CI: 1.85, 3.75) among participants exposed to the campaign compared with those not exposed to the campaign.…”
Section: Methodological Quality Of Included Studiessupporting
confidence: 67%
See 2 more Smart Citations
“…Similar positive impacts of being exposed to a campaign focussing on the importance of reducing the consumption of SSBs were also reported in two cross-sectional studies conducted in the US (Barragan et al, 2014;Robles et al, 2015). One of them (Barragan et al, 2014) reported more than twice the likelihood of correctly reporting the quantity of sugar in a soda drink (OR 2.63, 95%CI: 1.85, 3.75) among participants exposed to the campaign compared with those not exposed to the campaign.…”
Section: Methodological Quality Of Included Studiessupporting
confidence: 67%
“…One of them (Barragan et al, 2014) reported more than twice the likelihood of correctly reporting the quantity of sugar in a soda drink (OR 2.63, 95%CI: 1.85, 3.75) among participants exposed to the campaign compared with those not exposed to the campaign. The second (Robles et al, 2015) found that moderate consumers (1-6 sodas/week) were nearly twice as likely to reduce SSB intake (OR 1.95, 95%CI 1.44, 2.65) after exposure to the campaign, compared with heavy consumers (≥ 1 soda/day). Though both these cross-sectional studies analysed the same data and had a large sample of adults (n=1041), both may be at risk of selection bias as the sample was recruited from selected public transit locations.…”
Section: Methodological Quality Of Included Studiesmentioning
confidence: 97%
See 1 more Smart Citation
“…15 Kelly et al investigated the impact of television advertising on children's negative dietary patterns and found that the link between television viewing and poor diet was strongest for children who watched the greatest amount of commercial television, because they were heavily exposed to advertisements. 16 Although the aim of those studies was different from the present one, those studies indicate that pediatric health-care providers [17][18][19][20] It is necessary to consider a campaign that raises awareness of the appropriate use of ionic beverages in infants and young children.…”
Section: Discussionmentioning
confidence: 96%
“…Although the aim of those studies was different from the present one, those studies indicate that pediatric health‐care providers should be aware of ionic beverage consumption by infants and young children and should protect them from the unfavorable effects of advertisements by educating parents. Moreover, restricting food advertisements tends to improve dietary habits . It is necessary to consider a campaign that raises awareness of the appropriate use of ionic beverages in infants and young children.…”
Section: Discussionmentioning
confidence: 99%